Shear Behavior Simulation of Reinforced Concrete Beam Incorporating Glass Fibber-Reinforced Polymer Shear Reinforcement - Sutrisno, Rahmat Dwi; Sutrisno, Wahyuniarsih; Alrasyid, Harun; Piscesa, Bambang; Irmawan, Mudji (Journal of Civil Engineering, 2024)
This paper presents the shear behavior of concrete beams incorporating glass fiber-reinforced polymer (GFRP) stirrups using a nonlinear finite element simulation package, 3D-NLFEA. The experimental data was adopted from the test results performed by previous researchers. The constitutive model for the concrete material used in this simulation is based on the plasticity-fracture model and considers the tension-stiffening effect of the concrete. The numerical simulation result was compared with the experimental test, including the ultimate shear force-deflection response and cracking pattern. Based on the analysis result, it was found that the ultimate shear force-deflection response shows almost the same. For the mean ratio of prediction ultimate shear load to actual ultimate shear load from the experimental result and a coefficient of variation of 1.000 and 0.206%, respectively, and deformation results, the mean ratio of prediction deformations for the mid-shear span and mid-span of 0.966 and 0.941, respectively, with the coefficient of variation for the mid shear span and mid-span of 11.849% and 7.627%, respectively. However, the cracking pattern mode of the beam shows good results, which complies with the experimental test.